Occurrence of schistosomiasis in Divinópolis-MG based on study of schoolchildren and surveys of disease notification - Karina Talita de Oliveira Santana; Kayo Vieira Teodorak Pego; Valeriana Valadares Pereira; Larissa Parrela Rodrigues; Juliana Vitalina Ferreira; Karla Nogueira de Oliveira; Maria Jaciara Ferreira Trindade; Hélio de Oliveira; Eduardo Sergio da Silva; Luciana Lara dos Santos; Débora de Oliveira Lopes (Sociedade Brasileira de Patologia Clínica, 2014)
Introduction: Schistosomiasis is a neglected chronic disease that affects mainly underdeveloped regions, including Brazil. Objective: To evaluate the distribution profile of the schistosomiasis in Divinópolis-MG. Material and methods: It is characterized as a descriptive and analytical epidemiological study. A parasitological study performed in schoolchildren of public municipal schools; simultaneously, a survey of schistosomiasis cases reported in the city between 2005 and 2011 years was performed with the Municipal Department of Health. Data related to the characteristics of the infection were observed, such as: affected areas, age, gender, and professional occupation. Results: This survey showed 33 cases of schistosomiasis in the city during this period, which the most of them (84.8%) were between 20-59 years of age. The results of the study with the schoolchildren are in agreement with those obtained through the reporting forms, both indicating no occurrence of schistosomiasis in individuals between 6-14 years of age in Divinópolis. Conclusion: The absence of the disease in children and adolescents analyzed and the presence in adults is a strong evidence of exogenous contamination in the city, especially as a result of immigration or rural tourism, and possible changes in habits, related to risk factors.